Patterns of Sedentary Behavior in the First Month After Acute Coronary Syndrome. Issue 15 (6th August 2019) - Duran, Andrea T.; Ewing Garber, Carol; Cornelius, Talea; Schwartz, Joseph E.; Diaz, Keith M.
Abstract : Background: Sedentary behavior is a key contributor to cardiovascular disease. Few data exist on the sedentary behavior patterns of patients with acute coronary syndrome. Methods and Results: We characterized patterns of sedentary time and their correlates in 149 patients with acute coronary syndrome over the first month postdischarge, a critical period when lifestyle behaviors are formed. Sedentary time was measured by accelerometry for 28 days postdischarge. Group‐based modeling at the day level was used to characterize sedentary patterns. Participants spent a mean of 9.7±2.0 hours per day sedentary during the 28 days postdischarge, with significant decreases in sedentary time observed in each consecutive week ( P <0.01 for all). Three distinct sedentary patterns were identified: high (20.6% of participants), moderate (47.9%), and low (31.5%). The high and moderate sedentary groups spent a mean of 12.6±0.8 and 10.0±0.7 hours per day sedentary, respectively, and had only minimal decreases in their sedentary time (<3 minutes per day) over the 28 days. The low sedentary group spent a mean of 7.3±0.8 hours per day sedentary, with a rapid decrease in sedentary time (14 minutes per day) observed during the first week postdischarge followed by a relatively smaller decrease (≈5 minutes per day) that persisted until day 21 postdischarge. Non‐Hispanic ethnicity, left ventricular ejection fraction <40%, lower physical health–related quality of life, and not having a partner were associated with an increased likelihood of being in the high sedentary group. Conclusions: Survivors of acute coronary syndrome accrued high volumes of sedentary time during the first month postdischarge, with most showing little change over time. Interventions targeting reductions in sedentary time among survivors of acute coronary syndrome may be warranted, particularly for those with poor physical health and greater disease severity.